Myocardial injury in dogs with snake envenomation and its relation to systemic inflammation. (4th December 2013) - Langhorn, Rebecca; Persson, Frida; Åblad, Björn; Goddard, Amelia; Schoeman, Johan P.; Willesen, Jakob L.; Tarnow, Inge; Kjelgaard‐Hansen, Mads
Abstract Objective To investigate the presence of myocardial injury in dogs hospitalized for snake envenomation and to examine its relationship with systemic inflammation. Design Prospective case‐control study. Setting University teaching hospital and small animal referral hospital. Animals Dogs naturally envenomed by the European viper (Vipera berus; n = 24), African puff adder (Bitis arietans; n = 5), or snouted cobra (Naja annulifera; n = 9). Interventions Blood was collected from dogs envenomed by V. berus at admission, 12–24 hours postadmission, and 5–10 days postadmission. Blood was collected from dogs envenomed by B. arietans or N. annulifera at admission, and 12, 24, and 36 hours postadmission. Measurements and Main Results Concentrations of cardiac troponin I (cTnI), a marker of myocardial injury, and C‐reactive protein (CRP), a marker of systemic inflammation, were measured in each blood sample. Evidence of myocardial injury was found in 58% of dogs envenomed by V. berus at one or more time points. A significant correlation between cTnI and CRP concentrations was found at all time points. Evidence of myocardial injury was found in 80% of dogs envenomed by B. arietans at one or more time points; however, no correlation was found between cTnI and CRP concentrations. Evidence of myocardial injury was found in 67% of dogs envenomed by N. annulifera at one or more time points. A significant correlation between cTnI and CRP concentrations was found at admission, but not at other time points. Conclusions Myocardial injury frequently occurred in dogs with snake envenomation. While the degree of systemic inflammation was significantly correlated with degree of myocardial injury in V. berus envenomation at all time points, this was not the case in dogs envenomed by N. annulifera or B. arietans. This could be due to differences in the toxic substances of the snake venoms or to differences in the cytokines induced by the venom toxins.